ChemInform Abstract: An Efficient Route to Coumarin Derivatives under Dual Catalysis, an Organo‐ and a Lewis Acid Catalyst. Issue 9 (5th March 2013) - Maiti, Gourhari; Karmakar, Rajiv; Kayal, Utpal; Bhattacharya, Rudraksha Nath
Abstract A novel simple method is developed for the synthesis of coumarin derivatives (III) from salicylaldehydes and diesters such as (II) in the presence of FeCl3 and piperidine.